Electrolyte for alkaline aluminum-air battery, preparation method thereof, air battery and application
Patent Information
- Application Number
- CN202611517525.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-29
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]然而,现有碱性铝空气电池电解液技术存在以下不足:单纯使用KOH或NaOH作为碱性电解液时,铝在强碱中析氢腐蚀严重,造成大量铝在非有效放电过程中被消耗;而现有普通碱性电解液体系又难以同时兼顾高导电性、较高放电电流密度与较低析氢速率,往往出现提高放电活性后腐蚀加剧、抑制腐蚀后电流密度下降的矛盾
[0023]通过氢氧化钾、高锰酸钾、6-巯基嘌呤单水和氧化锌的复配,在一个体系内兼顾了导电性、放电活性和抑氢性能,不再局限于单一助剂改性思路。
Smart Images

Figure CN123018261A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal-air battery technology, and more specifically, to an electrolyte for alkaline aluminum-air batteries, a method for preparing the electrolyte, and air batteries and their applications. Background Technology
[0002] Aluminum-air batteries use aluminum as the negative electrode active material and oxygen from the air as the positive electrode reactant, undergoing an electrochemical reaction in the presence of an electrolyte to output electrical energy. This system boasts advantages such as abundant resources, high theoretical discharge potential, low cost, and environmental friendliness, making it highly promising for applications in backup power, portable energy storage, and specialized power supplies.
[0003] Currently, aluminum-air batteries can be classified into neutral and alkaline systems based on the electrolyte type. Neutral systems typically use NaCl solution or seawater as the electrolyte, but aluminum easily forms an Al(OH)3 precipitate layer on its surface in a neutral environment, leading to increased interfacial resistance, lower conductivity, and lower discharge potential, making it difficult to meet the application requirements of high current density and high discharge potential.
[0004] Therefore, alkaline electrolyte systems are typically used in applications requiring higher current density and discharge potential. Existing alkaline aluminum-air batteries usually use KOH or NaOH aqueous solutions as the base electrolyte. The aluminum anode maintains high discharge activity under alkaline conditions, resulting in relatively high battery output potential and current density. To improve discharge performance and anode utilization, current technologies often adjust the alkali concentration or add a single additive to enhance electrolyte performance.
[0005] However, existing alkaline aluminum-air battery electrolyte technologies have the following shortcomings: when using KOH or NaOH as the alkaline electrolyte alone, aluminum suffers severe hydrogen evolution corrosion in the strong alkali, resulting in a large amount of aluminum being consumed during ineffective discharge; and existing common alkaline electrolyte systems struggle to simultaneously achieve high conductivity, high discharge current density, and low hydrogen evolution rate, often resulting in a contradiction between increased corrosion after improving discharge activity and decreased current density after suppressing corrosion. This leads to the capacity density of existing aluminum-air batteries typically being less than 800 mAh / gAl, limiting their high specific energy applications; some additive systems in existing technologies suffer from single-function and insufficient synergy, making it difficult to simultaneously optimize from three aspects: promoting effective dissolution of the aluminum plate, improving conductivity, and suppressing hydrogen evolution side reactions, and lacking a systematic solution with a clearly defined composition and industrially scalable formulation. Therefore, there is an urgent need to provide an alkaline aluminum-air battery electrolyte and its preparation method to solve the above problems. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention provides an electrolyte for alkaline aluminum-air batteries and its preparation method. By synergistically compounding KOH, KMnO4, 6-mercaptopurine monohydrate, and ZnO, it balances conductivity, discharge activity, and hydrogen suppression performance, significantly improving anode utilization and capacity density, breaking through the 800 mAh / gAl limitation. Furthermore, the preparation is simple and easy to scale up in engineering.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows:
[0008] An electrolyte for an alkaline aluminum-air battery comprises the following components: 35-40 wt% potassium hydroxide; 0.2-0.6 wt% zinc oxide; 4-8 mmol / L 6-mercaptopurine monohydrate; 0.1-0.5 g / L potassium permanganate; and the balance being water.
[0009] As a preferred embodiment of the present invention, the amount of potassium hydroxide used is 37 wt%; the concentration of potassium permanganate is 0.2 g / L.
[0010] As a preferred embodiment of the present invention, the concentration of the 6-mercaptopurine monohydrate is 6 mmol / L.
[0011] As a preferred embodiment of the present invention, the amount of zinc oxide used is 0.3 wt%.
[0012] A method for preparing an electrolyte for an alkaline aluminum-air battery includes the following steps:
[0013] S1. Determine the amount of potassium hydroxide to be used according to the mass fraction of potassium hydroxide in the final electrolyte being 35-40 wt%. Add potassium hydroxide to the water of the amount determined according to the formula, stir to dissolve, and obtain the basic electrolyte.
[0014] S2. Add 0.2-0.6 wt% zinc oxide to the solution obtained in step S1 and stir to dissolve;
[0015] S3. After zinc oxide is dissolved, potassium permanganate is added to the solution obtained in S2, and stirring is continued until fully mixed, so that the concentration of potassium permanganate in the final electrolyte is 0.1-0.5 g / L;
[0016] S4. After the solution cools, add 6-mercaptopurine monohydrate to the solution obtained in S3 to make its final concentration in the final electrolyte 4-8 mmol / L, thus obtaining the electrolyte for alkaline aluminum-air batteries.
[0017] As a preferred embodiment of the present invention, the concentration of potassium hydroxide is 37 wt%, and the concentration of potassium permanganate in the final electrolyte in S3 is 0.2 g / L.
[0018] As a preferred embodiment of the present invention, the final concentration of 6-mercaptopurine monohydrate in S4 in the final electrolyte is 6 mmol / L.
[0019] As a preferred embodiment of the present invention, the amount of zinc oxide used in S2 is 0.3 wt%.
[0020] An aluminum-air battery includes an aluminum negative electrode, an air positive electrode, and the aforementioned alkaline aluminum-air battery electrolyte.
[0021] The above-mentioned alkaline aluminum-air battery electrolyte is used to improve the discharge current, capacity density, or anode utilization rate of aluminum-air batteries.
[0022] The beneficial effects of this invention are:
[0023] By combining potassium hydroxide, potassium permanganate, 6-mercaptopurine monohydrate and zinc oxide, conductivity, discharge activity and hydrogen suppression performance are taken into account in one system, which is no longer limited to the idea of modifying with a single auxiliary agent.
[0024] The thiol group (-SH) of 6-mercaptopurine monohydrate is located at the 6-position of the purine ring. The sulfur atom on the thiol group contains a lone pair of electrons, exhibiting strong electron-donating ability and nucleophilicity. The purine fused-ring system contains multiple nitrogen atoms (N1, N3, N7, etc.), which also possess lone pairs of electrons and can serve as coordination sites. The purine ring itself has a large π-bond system, which can interact electronically with metal surfaces. 6-mercaptopurine monohydrate possesses the chemical basis for coordination or adsorption with various metal ions and metal surfaces.
[0025] The thiol group (-SH) can be deprotonated under alkaline conditions to form a sulfide anion (-S). - The lone pair of electrons on the sulfur atom can be transferred to Zn. 2+ The empty orbitals of the nitrogen atom in the purine ring donate electrons to form coordinate bonds. The nitrogen atoms N1, N3, and N7 on the purine ring also contain lone pairs of electrons, which can act as electron pair donors to bond with Zn. 2+ Coordination occurs. 6-Mercaptopurine can simultaneously bind to the same Zn atom via a sulfur atom and multiple nitrogen atoms. 2+ Coordination forms a stable chelate ring structure.
[0026] 6-Mercaptopurine molecules adsorb directly onto the aluminum surface via sulfur and nitrogen atoms, and also interact with Zn in solution through the same functional groups. 2+ Zincate species coordination. This dual effect allows 6-mercaptopurine molecules to act as molecular bridges, anchoring zinc ions near the aluminum surface and forming an in-situ metal-organic complex network on top of the zinc oxide deposit. The 6-mercaptopurine molecules adsorbed on the aluminum surface can then act as anchor points, continuing to interact with more Zn in the solution. 2+It coordinates with 6-mercaptopurine molecules to form a multi-layered, dense protective film. When a local film is damaged due to aluminum dissolution, 6-mercaptopurine and zinc species in the solution can be rapidly re-adsorbed and coordinated on the exposed fresh aluminum surface, achieving self-repair of the film.
[0027] This electrolyte can effectively increase the dissolution rate of the aluminum anode, improve the discharge potential and discharge current density of the aluminum-air battery, and enhance output performance.
[0028] Compared to ordinary alkaline electrolytes, this invention helps to improve the capacity density of aluminum-air batteries, overcoming the limitation of existing technologies where the capacity density is usually less than 800 mAh / gAl.
[0029] The technical solution has a clear composition, simple preparation steps, and is easy to implement, making it suitable for laboratory preparation and further engineering scale-up. Attached Figure Description
[0030] Figure 1 This is a schematic diagram of the method flow of the present invention.
[0031] Figure 2 This is a data comparison table for the present invention. Detailed Implementation
[0032] In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0033] Combination Figures 1-2 The present invention provides the following embodiments:
[0034] In this application, the mass percentages of potassium hydroxide and zinc oxide are based on the total mass of the final electrolyte; the molar concentrations of 6-mercaptopurine monohydrate and potassium permanganate are based on the volume of the final electrolyte.
[0035] Example 1:
[0036] Electrolyte preparation includes the following steps:
[0037] Step 1. Determine the amount of potassium hydroxide to be used based on the final electrolyte mass fraction of 37wt%. Add the potassium hydroxide to the deionized water of the amount determined according to the formula and stir to dissolve.
[0038] Step 2. Add 0.3 wt% zinc oxide to the above solution and stir to dissolve at room temperature;
[0039] Step 3. After the zinc oxide has completely dissolved, add 0.2 g / L of potassium permanganate and continue stirring for 15 minutes until fully mixed;
[0040] Step 4. Cool the solution naturally to room temperature (25°C), add 6-mercaptopurine monohydrate to make the final concentration 6 mmol / L, and continue stirring for 15 min to obtain the alkaline aluminum-air battery electrolyte.
[0041] Battery assembly and testing: The negative electrode uses a 3N9 pure aluminum plate with a purity of 99.9%; the positive electrode uses a commercially available air electrode, whose main components are manganese dioxide, acetylene black, and nickel mesh. The electrolyte volume is 100 mL, and the test temperature is 25°C. The current density is 20 mA / cm². 2 A constant current discharge is performed, with a cutoff voltage of 0.5 V, and the actual working area of the aluminum plate is 4 cm². 2 Specifically, 2cm 2cm; record the stable operating voltage and calculate the capacity density and anode utilization rate. The corrosion rate of the aluminum anode was determined using the static immersion weight loss method, independent of the discharge test. All groups used the same immersion conditions, and the corrosion rate was calculated as the ratio of the mass loss of the aluminum anode before and after immersion to the immersion time, expressed in mg / h.
[0042] Test results: The stable operating voltage is 1.23V, the capacity density calculated based on the mass of the aluminum anode is 2487mAh / g, and the corrosion rate of the aluminum anode is 18mg / h.
[0043] Example 2:
[0044] Electrolyte preparation:
[0045] Step 1. Determine the amount of potassium hydroxide to be used based on the final electrolyte mass fraction of 37wt%. Add the potassium hydroxide to the deionized water of the amount determined according to the formula and stir to dissolve.
[0046] Step 2. Add 0.3 wt% zinc oxide to the above solution and stir to dissolve at room temperature;
[0047] Step 3. After the zinc oxide has completely dissolved, add 0.2 g / L of potassium permanganate and continue stirring for 15 minutes until fully mixed;
[0048] Step 4. Cool the solution naturally to room temperature (25°C), add 6-mercaptopurine monohydrate to make the final concentration 4 mmol / L, and continue stirring for 15 min to obtain the alkaline aluminum-air battery electrolyte.
[0049] Battery assembly and testing: Same as in Example 1.
[0050] Test results: The stable operating voltage is 1.14V, the capacity density calculated based on the mass of the aluminum anode is 2047mAh / g, and the corrosion rate of the aluminum anode is 34mg / h.
[0051] Example 3:
[0052] Electrolyte preparation:
[0053] Step 1. Determine the amount of potassium hydroxide to be used based on the final electrolyte mass fraction of 37wt%. Add the potassium hydroxide to the deionized water of the amount determined according to the formula and stir to dissolve.
[0054] Step 2. Add 0.3 wt% zinc oxide to the above solution and stir to dissolve at room temperature;
[0055] Step 3. After the zinc oxide has completely dissolved, add 0.2 g / L of potassium permanganate and continue stirring for 15 minutes until fully mixed;
[0056] Step 4. Allow the solution to cool naturally to room temperature (25°C), add 6-mercaptopurine monohydrate to make a final concentration of 8 mmol / L, and continue stirring for 15 min to obtain the alkaline aluminum-air battery electrolyte.
[0057] Battery assembly and testing: Same as in Example 1.
[0058] Test results: The stable operating voltage is 1.21V, the capacity density calculated based on the mass of the aluminum anode is 2375mAh / g, and the corrosion rate of the aluminum anode is 22mg / h.
[0059] Example 4:
[0060] Electrolyte preparation:
[0061] Step 1. Determine the amount of potassium hydroxide to be used based on the final electrolyte mass fraction of 37wt%. Add the potassium hydroxide to the deionized water of the amount determined according to the formula and stir to dissolve.
[0062] Step 2. Add 0.2 wt% zinc oxide to the above solution and stir to dissolve at room temperature;
[0063] Step 3. After the zinc oxide has completely dissolved, add 0.2 g / L of potassium permanganate and continue stirring for 15 minutes until fully mixed;
[0064] Step 4. Cool the solution naturally to room temperature (25°C), add 6-mercaptopurine monohydrate to make the final concentration 6 mmol / L, and continue stirring for 15 min to obtain the alkaline aluminum-air battery electrolyte.
[0065] Battery assembly and testing: Same as in Example 1.
[0066] Test results: The stable operating voltage is 1.19V, the capacity density calculated based on the mass of the aluminum anode is 2264mAh / g, and the corrosion rate of the aluminum anode is 24mg / h.
[0067] Example 5:
[0068] Electrolyte preparation:
[0069] Step 1. Determine the amount of potassium hydroxide to be used based on the final electrolyte mass fraction of 37wt%. Add the potassium hydroxide to the deionized water of the amount determined according to the formula and stir to dissolve.
[0070] Step 2. Add 0.6 wt% zinc oxide to the above solution and stir to dissolve at room temperature;
[0071] Step 3. After the zinc oxide has completely dissolved, add 0.2 g / L of potassium permanganate and continue stirring for 15 minutes until fully mixed;
[0072] Step 4. Cool the solution to 25°C, add 6-mercaptopurine monohydrate to make the final concentration 6 mmol / L, and continue stirring for 15 min to obtain the alkaline aluminum-air battery electrolyte.
[0073] Battery assembly and testing: Same as in Example 1.
[0074] Test results: The stable operating voltage is 1.16V, the capacity density calculated based on the mass of the aluminum anode is 2153mAh / g, and the corrosion rate of the aluminum anode is 27mg / h.
[0075] Example 6:
[0076] Electrolyte preparation includes the following steps:
[0077] Step 1. Determine the amount of potassium hydroxide to be used based on the final electrolyte having a mass fraction of 35 wt%. Add the potassium hydroxide to the deionized water of the amount determined according to the formula and stir to dissolve.
[0078] Step 2. Add 0.3 wt% zinc oxide to the above solution and stir to dissolve at room temperature;
[0079] Step 3. After the zinc oxide has completely dissolved, add 0.1 g / L potassium permanganate and continue stirring for 15 min until fully mixed;
[0080] Step 4. Cool the solution naturally to room temperature (25 °C), add 6-mercaptopurine monohydrate to make the final concentration 6 mmol / L, and continue stirring for 15 min to obtain the electrolyte for alkaline aluminum-air batteries.
[0081] Battery assembly and testing: Same as in Example 1.
[0082] Test results: The stable operating voltage is 1.19 V, the capacity density calculated based on the mass of the aluminum anode is 2320 mAh / g, and the corrosion rate of the aluminum anode is 22 mg / h.
[0083] Example 7:
[0084] Electrolyte preparation includes the following steps:
[0085] Step 1. Determine the amount of potassium hydroxide to be used based on the final electrolyte having a mass fraction of 40 wt%. Add the potassium hydroxide to the deionized water of the amount determined according to the formula and stir to dissolve.
[0086] Step 2. Add 0.3 wt% zinc oxide to the above solution and stir to dissolve at room temperature;
[0087] Step 3. After the zinc oxide has completely dissolved, add 0.1 g / L potassium permanganate and continue stirring for 15 min until fully mixed;
[0088] Step 4. Cool the solution naturally to room temperature (25 °C), add 6-mercaptopurine monohydrate to make the final concentration 6 mmol / L, and continue stirring for 15 min to obtain the electrolyte for alkaline aluminum-air batteries.
[0089] Battery assembly and testing: Same as in Example 1.
[0090] Test results: The stable operating voltage is 1.17 V, the capacity density calculated based on the mass of the aluminum anode is 2250 mAh / g, and the corrosion rate of the aluminum anode is 25 mg / h.
[0091] Example 8:
[0092] Electrolyte preparation includes the following steps:
[0093] Step 1. Determine the amount of potassium hydroxide to be used based on the final electrolyte having a mass fraction of 35 wt%. Add the potassium hydroxide to the deionized water of the amount determined according to the formula and stir to dissolve.
[0094] Step 2. Add 0.3 wt% zinc oxide to the above solution and stir to dissolve at room temperature;
[0095] Step 3. After the zinc oxide has completely dissolved, add 0.5 g / L potassium permanganate and continue stirring for 15 min until fully mixed;
[0096] Step 4. Cool the solution naturally to room temperature (25 °C), add 6-mercaptopurine monohydrate to make the final concentration 6 mmol / L, and continue stirring for 15 min to obtain the electrolyte for alkaline aluminum-air batteries.
[0097] Battery assembly and testing: Same as in Example 1.
[0098] Test results: The stable operating voltage is 1.16 V, the capacity density calculated based on the mass of the aluminum anode is 2190 mAh / g, and the corrosion rate of the aluminum anode is 24 mg / h.
[0099] Example 9:
[0100] Electrolyte preparation includes the following steps:
[0101] Step 1. Determine the amount of potassium hydroxide to be used based on the final electrolyte having a mass fraction of 40 wt%. Add the potassium hydroxide to the deionized water of the amount determined according to the formula and stir to dissolve.
[0102] Step 2. Add 0.3 wt% zinc oxide to the above solution and stir to dissolve at room temperature;
[0103] Step 3. After the zinc oxide has completely dissolved, add 0.5 g / L potassium permanganate and continue stirring for 15 min until fully mixed;
[0104] Step 4. Cool the solution naturally to room temperature (25 °C), add 6-mercaptopurine monohydrate to make the final concentration 6 mmol / L, and continue stirring for 15 min to obtain the electrolyte for alkaline aluminum-air batteries.
[0105] Battery assembly and testing: Same as in Example 1.
[0106] Test results: The stable operating voltage is 1.14 V, the capacity density calculated based on the mass of the aluminum anode is 2130 mAh / g, and the corrosion rate of the aluminum anode is 28 mg / h.
[0107] Comparative Example 1:
[0108] Electrolyte preparation:
[0109] Step 1. Determine the amount of potassium hydroxide to be used based on the final electrolyte mass fraction of 37wt%. Add the potassium hydroxide to the deionized water of the amount determined according to the formula and stir to dissolve.
[0110] Step 2. Add 0.3 wt% zinc oxide to the above solution and stir to dissolve at room temperature;
[0111] Step 3. After the zinc oxide has completely dissolved, add 0.2 g / L of potassium permanganate and continue stirring for 15 minutes until fully mixed;
[0112] Step 4. Cool the solution to 25°C to obtain the alkaline aluminum-air battery electrolyte.
[0113] Battery assembly and testing: Same as in Example 1.
[0114] Test results: The stable operating voltage is 1.18V, the capacity density calculated based on the mass of the aluminum anode is 2003mAh / g, and the corrosion rate of the aluminum anode is 45mg / h.
[0115] Comparative Example 2:
[0116] Electrolyte preparation:
[0117] Step 1. Determine the amount of potassium hydroxide to be used based on the final electrolyte mass fraction of 37wt%. Add the potassium hydroxide to the deionized water of the amount determined according to the formula and stir to dissolve.
[0118] Step 2. Add 0.3 wt% zinc oxide to the above solution and stir to dissolve at room temperature;
[0119] Step 3. After the zinc oxide has completely dissolved, add 0.2 g / L of potassium permanganate and continue stirring for 15 minutes until fully mixed;
[0120] Step 4. Cool the solution to 25°C, add 6-mercaptopurine monohydrate to make the final concentration 2 mmol / L, and continue stirring for 15 min to obtain the alkaline aluminum-air battery electrolyte.
[0121] Battery assembly and testing: Same as in Example 1.
[0122] Test results: The stable operating voltage is 1.12V, the capacity density calculated based on the mass of the aluminum anode is 2052mAh / g, and the corrosion rate of the aluminum anode is 37mg / h.
[0123] Comparative Example 3:
[0124] Electrolyte preparation:
[0125] Step 1. Determine the amount of potassium hydroxide to be used based on the final electrolyte mass fraction of 37wt%. Add the potassium hydroxide to the deionized water of the amount determined according to the formula and stir to dissolve.
[0126] Step 2. Add 0.2 g / L potassium permanganate and continue stirring for 15 minutes until fully mixed;
[0127] Step 3. Cool the solution to 25°C, add 6-mercaptopurine monohydrate to make the final concentration 6 mmol / L, and continue stirring for 15 min to obtain the alkaline aluminum-air battery electrolyte.
[0128] Battery assembly and testing: Same as in Example 1.
[0129] Test results: The stable operating voltage is 1.05V, the capacity density calculated based on the mass of the aluminum anode is 2103mAh / g, and the corrosion rate of the aluminum anode is 30mg / h.
[0130] The simple summation of the expected corrosion rates of Comparative Examples 1 and 3 was approximately (45+30) / 2 = 37.5 mg / h, while the actual corrosion rate of Example 1 was only 18 mg / h, far lower than the expected linear summation, representing a reduction of up to 52%. This fully demonstrates the strong synergistic inhibitory effect between ZnO and 6-mercaptopurine. 6-Mercaptopurine, through its thiol sulfur atom and purine ring nitrogen atom, simultaneously coordinates / adsorbs with the active sites on the aluminum surface and the zinc species deposition layer, constructing a dense metal-organic complex network in situ on the inorganic deposition layer, filling the pores of the film and effectively isolating water molecules from contact with the aluminum substrate.
[0131] The results analysis proves
[0132] The results of Examples 1, 2, and 3 collectively demonstrate that when the concentration of 6-mercaptopurine monohydrate is in the range of 4–8 mmol / L, the electrolyte can improve the discharge performance of the aluminum anode and reduce ineffective corrosion consumption. Among them, when the concentration of 6-mercaptopurine monohydrate is 6 mmol / L, the combination between the organic adsorption / coordination components and zinc species in the electrolyte is more suitable, resulting in better overall performance.
[0133] Examples 1, 4, and 5 were used to investigate the effect of zinc oxide dosage on electrolyte performance. The results show that when the zinc oxide dosage is in the range of 0.2–0.6 wt%, the electrolyte can provide zinc species to participate in the interface regulation of the aluminum anode; among them, when the zinc oxide dosage is 0.3 wt%, the zinc species concentration is well matched with the 6-mercaptopurine monohydrate concentration, which is conducive to the formation of a more stable interfacial adsorption / coordination.
[0134] Compared with Comparative Example 1, Example 1 demonstrates that adding 6-mercaptopurine monohydrate to the KOH, ZnO, and KMnO4 base system enhances the inhibitory effect of the electrolyte on the ineffective corrosion consumption of the aluminum anode and is beneficial for increasing the capacity density. Therefore, 6-mercaptopurine monohydrate is an important component that distinguishes the electrolyte of this invention from the basic alkaline compound system.
[0135] Compared with Comparative Example 2, Example 1 demonstrates that when the concentration of 6-mercaptopurine monohydrate is below the range defined in this invention, its adsorption / coordination protection effect on the aluminum anode surface is insufficient, making it difficult to fully exert the effects of inhibiting corrosion and increasing capacity density. Therefore, limiting the concentration of 6-mercaptopurine monohydrate to 4–8 mmol / L is reasonable.
[0136] Compared with Comparative Example 3, Example 1 demonstrates that when only 6-mercaptopurine monohydrate is added without zinc oxide, the electrolyte lacks zinc species that coordinate with 6-mercaptopurine monohydrate, thus weakening the interfacial protection. This indicates a synergistic effect between 6-mercaptopurine monohydrate and the zinc species formed by the dissolution of zinc oxide.
[0137] Examples 6, 7, 8, and 9 were used to investigate the effects of potassium hydroxide concentration and potassium permanganate dosage on electrolyte performance when they were within the limits defined by this invention. In the above examples, the zinc oxide dosage was maintained at 0.3 wt%, the 6-mercaptopurine monohydrate concentration was maintained at 6 mmol / L, the potassium hydroxide concentration was set to 35 wt% and 40 wt%, and the potassium permanganate dosage was set to 0.1 g / L and 0.5 g / L, thus forming different combinations of boundary parameters.
[0138] The results of Examples 6 and 7, and Examples 8 and 9, collectively demonstrate that when the amounts of zinc oxide, 6-mercaptopurine monohydrate, and potassium permanganate are the same, and the potassium hydroxide concentrations are 35 wt% and 40 wt%, respectively, the resulting electrolytes can maintain normal discharge of the aluminum-air battery and exhibit similar and relatively stable overall performance in terms of stable operating voltage, capacity density, and aluminum anode corrosion rate. This indicates that within the potassium hydroxide concentration range of 35–40 wt%, the electrolyte can provide the alkaline environment required for alkaline aluminum-air battery discharge, while maintaining good compatibility with the compound system composed of zinc oxide, 6-mercaptopurine monohydrate, and potassium permanganate.
[0139] The results of Examples 6 and 8, and Examples 7 and 9, collectively demonstrate that, under the same conditions of potassium hydroxide concentration, zinc oxide dosage, and 6-mercaptopurine monohydrate concentration, when the potassium permanganate dosage is 0.1 g / L and 0.5 g / L, respectively, the resulting electrolytes can improve discharge performance and inhibit ineffective corrosion of the aluminum anode. This indicates that potassium permanganate, within the range of 0.1–0.5 g / L, can participate in the interface regulation of the aluminum anode and form a stable complex inhibition system in combination with zinc oxide and 6-mercaptopurine monohydrate.
[0140] Furthermore, all four sets of experiments were able to achieve the expected stable operating voltage, capacity density, and corrosion inhibition effect.
[0141] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. An electrolyte for alkaline aluminum-air batteries, characterized in that, It comprises the following components: potassium hydroxide 35–40 wt%; zinc oxide 0.2–0.6 wt%; 6-mercaptopurine monohydrate 4–8 mmol / L; potassium permanganate 0.1–0.5 g / L; the balance being water.
2. The electrolyte for alkaline aluminum-air batteries according to claim 1, characterized in that, The amount of potassium hydroxide used is 37 wt%; the concentration of potassium permanganate is 0.2 g / L.
3. The electrolyte for alkaline aluminum-air batteries according to claim 1, characterized in that, The concentration of the 6-mercaptopurine monohydrate is 6 mmol / L.
4. The electrolyte for alkaline aluminum-air batteries according to claim 1, characterized in that, The amount of zinc oxide used is 0.3 wt%.
5. A method for preparing an electrolyte for an alkaline aluminum-air battery as described in any one of claims 1-4, characterized in that, Includes the following steps: S1. Determine the amount of potassium hydroxide to be used according to the mass fraction of potassium hydroxide in the final electrolyte being 35-40 wt%. Add potassium hydroxide to the water of the amount determined according to the formula, stir to dissolve, and obtain the basic electrolyte. S2. Add 0.2-0.6 wt% zinc oxide to the solution obtained in S1 and stir to dissolve; S3. After zinc oxide is dissolved, potassium permanganate is added to the solution obtained in S2, and stirring is continued until fully mixed, so that the concentration of potassium permanganate in the final electrolyte is 0.1-0.5 g / L; S4. After the solution cools, add 6-mercaptopurine monohydrate to the solution obtained in S3 to make its final concentration in the final electrolyte 4-8 mmol / L, thus obtaining the electrolyte for alkaline aluminum-air batteries.
6. The method for preparing the electrolyte for an alkaline aluminum-air battery according to claim 5, characterized in that, The concentration of potassium hydroxide is 37 wt%; the concentration of potassium permanganate in S3 in the final electrolyte is 0.2 g / L.
7. The method for preparing the electrolyte for an alkaline aluminum-air battery according to claim 5, characterized in that, The final concentration of 6-mercaptopurine monohydrate in S4 in the final electrolyte is 6 mmol / L.
8. The method for preparing the electrolyte for an alkaline aluminum-air battery according to claim 5, characterized in that, The amount of zinc oxide used in S2 is 0.3 wt%.
9. An aluminum-air battery, characterized in that, It includes an aluminum negative electrode, an air positive electrode, and an electrolyte for alkaline aluminum-air batteries as described in any one of claims 1 to 4.
10. The use of the alkaline aluminum-air battery electrolyte as described in any one of claims 1 to 4 in improving the discharge current, capacity density, or anode utilization rate of an aluminum-air battery.